Ab initio nonequilibrium molecular dynamics in the solid superionic conductor LiBH4. - Aeberhard, P; Williams, SR; Evans, D; Refson, K; David, W (2012)
The color-diffusion algorithm is applied to ab initio molecular dynamics simulation of hexagonal LiBH(4) to determine the lithium diffusion coefficient and diffusion mechanisms. Even in the best solid lithium ion conductors, the time scale of ion diffusion is too long to be readily accessible by ab initio molecular dynamics at a reasonable computational cost. In our nonequilibrium method, rare events are accelerated by the application of an artificial external field acting on the mobile species; the system response to this perturbation is accurately described in the framework of linear response theory and is directly related to the diffusion coefficient, thus resulting in a controllable approximation. The calculated lithium ionic conductivity of LiBH(4) closely matches published measurements, and the diffusion mechanism can be elucidated directly from the generated trajectory.